Effectiveness of Ketoprofen Suppositories in Reducing the Risk of Preterm Labor at a Teaching Hospital in Malang - Tri Isworowati; Budi Utomo; Ratna Dwi Jayanti (Jurnal Kebidanan Midwiferia, 2025)
Partus prematurus imminens (PPI) was a condition that threatened preterm labor, marked by labor signs before term (20 to <37 weeks) and birth weight under 2500 grams. Management included rest, hydration, and pharmacological measures. One approach used to delay labor was tocolytic therapy, such as ketoprofen suppositories, to inhibit uterine contractions. This study aimed to analyze the difference in uterine contractions before and after the administration of ketoprofen suppositories in women at risk of preterm labor. This study used a quasi-experimental design with a pre-test and post-test without a control group. The sample included 30 pregnant women with PPI who met the inclusion criteria. Consecutive sampling was used. The intervention administered was ketoprofen suppository therapy, 200 mg (2 tablets) given rectally. Data were collected using an observation sheet and analyzed using the Wilcoxon signed-rank test. The results showed that the mean uterine contraction score before therapy was 2,17, which decreased to 1,20 after therapy. There was a statistically significant difference in uterine contractions before and after the intervention. The Wilcoxon signed-rank test resulted in a p-value of 0,001 (p ≤ 0,05). The findings indicated a significant difference in uterine contractions before and after the administration of ketoprofen suppositories in pregnant women at risk of preterm labor. Ketoprofen suppository therapy was effective in reducing uterine contractions in pregnant women at risk of preterm labor, with routine fetal monitoring ensuring the safety of the intervention.